2009
DOI: 10.1210/en.2008-1648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Global Nutrient Restriction on Fetal Baboon Hepatic Insulin-Like Growth Factor System Genes and Gene Products

Abstract: Knowledge of altered maternal nutrition effects on growth-regulating systems is critical to understanding normal and abnormal fetal development. There are many reports of hepatic fetal IGF system responses to maternal nutrient restriction (MNR) during pregnancy in rodents and sheep but none in nonhuman primates. We determined effects of MNR on the fetal baboon hepatic IGF system. Social groups of female baboons were fed ad libitum, controls, or 70% controls (MNR) from 0.16 to 0.5 gestation and fetuses delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 32 publications
5
50
1
1
Order By: Relevance
“…In baboons, moderate maternal nutrition restriction (MNR) has only minor effects on overall fetal growth at 0.5 gestation (G -term 184 days) [7,8], but at 0.9G fetuses show intrauterine growth restriction [9]. Decreased maternal nutrition in pregnant baboons was shown to alter the placental nutrient transfer [10], fetal metabolism [7] and was associated with an increased risk for postnatal adverse outcomes such as insulin resistance [11]. Metabolic adaptations during development in response to decreased fetal nutrition may persist after birth, even when nutrition has returned to the normal range [12].…”
mentioning
confidence: 99%
“…In baboons, moderate maternal nutrition restriction (MNR) has only minor effects on overall fetal growth at 0.5 gestation (G -term 184 days) [7,8], but at 0.9G fetuses show intrauterine growth restriction [9]. Decreased maternal nutrition in pregnant baboons was shown to alter the placental nutrient transfer [10], fetal metabolism [7] and was associated with an increased risk for postnatal adverse outcomes such as insulin resistance [11]. Metabolic adaptations during development in response to decreased fetal nutrition may persist after birth, even when nutrition has returned to the normal range [12].…”
mentioning
confidence: 99%
“…Two recent studies have identified and profiled baboon liver miRNAs that are responsive to dietary fat and cholesterol (56). We and others have studied maternal and fetal baboon physiology in both normal pregnancy and following perturbations that led to developmental programming (65). We have shown that maternal overnutrition in sheep leads to impaired fetal cardiac function and altered insulin signaling (104).…”
mentioning
confidence: 99%
“…Interestingly, fetal liver glycogen as well as phosphoenolpyruvate carboxykinase (PEPCK), the rate-limiting enzyme for gluconeogenesis, is distributed similarly around the central lobular vein. 2,3 Numerous studies have suggested that one of the mechanisms by which catecholamines mobilize glucose from the liver in times of need is by stimulation of PEPCK via activation of b-ARs. 5,32,33 It is therefore plausible that localization of b-ARs, glycogen, and PEPCK around the central lobular vein is to maintain an adequate glucose status during fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Among the documented fetal hepatic responses to reduced nutrient availability in baboon pregnancy are altered functions of the insulin-like growth factor (IGF) axis including increased liver glycogen. 2 Since the fetal liver plays a central role in basal as well as perturbed fetal metabolic function, we have begun a series of studies to evaluate both normal ontogeny and responses to MNR. 2,3 Part of our rationale is the need to rectify the scarcity of information available on the ontogeny and physiological responses of fetal hepatic betaadrenergic receptors (b-ARs) to challenges such as reduced maternal nutrition.…”
Section: Introductionmentioning
confidence: 99%